Experience of surgical treatments for abdominal inferior vena cava injuries in a regional trauma center in Korea - Jin Woo Park; Dong Hun Kim (Journal of Trauma and Injury)
Purpose Inferior vena cava (IVC) injuries are a rare type of traumatic abdominal injuries that are challenging to treat and have a very high mortality rate. This study described our experience with the surgical treatment of traumatic IVC injuries, and we investigated the demographics, clinical profiles, and surgical outcomes of cases at a regional trauma center. Methods Among the 16 patients who were treated for a traumatic IVC injury between January 2014 and March 2022, 14 underwent surgery. The surgical outcomes included overall mortality and 24-hour mortality, and we investigated the factors associated with these surgical outcomes. The 14 patients were divided into two groups according to the location of the IVC injury (retrohepatic IVC or higher vs. subhepatic IVC), and differences between the two groups were analyzed. Results A body mass index (BMI) >23.0 kg/m2 (P=0.046), an elevated serum lactate level (P=0.043), and a shorter operation time (P=0.016) were associated with overall mortality. A higher BMI (P=0.050), higher serum lactate level (P=0.004), shorter operation time (P=0.005), and an injury at the retrohepatic IVC or higher level (P=0.031) were associated with 24-hour mortality. Younger age (P=0.028), higher BMI (P=0.005), more acidic pH, higher lactatemia (P=0.012), a higher hemoglobin level (P=0.012), and shorter door-to-operating room time (P=0.028) were associated with injury at the retrohepatic IVC or higher level. Patients with subhepatic IVC injuries had a high rate of direct repair (75.0%) and a significantly lower 24-hour mortality rate (37.5%, P=0.031). Conclusions Subhepatic IVC injuries are easy to access and are usually expected to treat with a direct repair method. Injuries at the retrohepatic IVC or higher level are difficult to treat surgically and require a systematic and multidisciplinary treatment strategy.